2023
DOI: 10.1039/d2sc05959b
|View full text |Cite
|
Sign up to set email alerts
|

Selective oxidation of silanes into silanols with water using [MnBr(CO)5] as a precatalyst

Abstract: This study presents the use of MnBr(CO)5 for the selective conversion of silanes to silanols with water as an oxidant generating valuable hydrogen as the only by-product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 64 publications
(41 reference statements)
1
5
0
Order By: Relevance
“…The water infiltrated into the nanonetwork seemed to trigger the reaction of unreacted functions during the nanofiber fabrication process as shown by the increase of the gel fractions (figure 3(C)) just after immersion in the degradation medium (PLA -Si-XL, (PLA/ G 40 −0.2%) -Si-XL, and (PLA/G 40 −2%) -Si-XL ). The aqueous catalysis of silane functions is well described in the literature as well as the water-ageing of this kind of materials [33,34]. According to our results, this new link formation occurred in the first three days, and did not interfere with the gradual decrease of the gel fraction over the following 30 d.…”
Section: Hybrid Nanofibers Degradationsupporting
confidence: 82%
“…The water infiltrated into the nanonetwork seemed to trigger the reaction of unreacted functions during the nanofiber fabrication process as shown by the increase of the gel fractions (figure 3(C)) just after immersion in the degradation medium (PLA -Si-XL, (PLA/ G 40 −0.2%) -Si-XL, and (PLA/G 40 −2%) -Si-XL ). The aqueous catalysis of silane functions is well described in the literature as well as the water-ageing of this kind of materials [33,34]. According to our results, this new link formation occurred in the first three days, and did not interfere with the gradual decrease of the gel fraction over the following 30 d.…”
Section: Hybrid Nanofibers Degradationsupporting
confidence: 82%
“…Following from this, auto-VTNA was applied to kinetic data from 22 publications, including stoichiometric and catalytic reactions (Table 4, entries 1-14) containing up to 6 reaction species (reactants, reagents, catalyst and additives). 5,8,9,34,[37][38][39][40][41][42][43][44][45][46] The current approach to VTNA experimentation involves performing a "standard" reaction, under synthetically relevant conditions, followed by "different excess" experiments, where only the initial concentration of each reaction species is altered.…”
Section: Automatic Determination Of Rate Equations Using Auto-vtnamentioning
confidence: 99%
“…Mechanism study based on spectroscopic techniques and the reaction kinetics shows that cationic tricarbonyl Mn(I) is the active species in the catalytic cycle (Scheme 5). [21] In addition, Chan and Meng described the dehydrogenative coupling of silanes with hydroxyl compounds (alcohols, phenols, indoles, and water) catalyzed by Mn(CO) 10 and phosphineoxide under heating conditions (> 91 examples, up to 99 % yield) (Scheme 6). In this study, they found phosphineoxide ligand is essential for this catalytic system, because the conversion of silane to silanol was slow in the absence of phosphineoxide.…”
Section: Mn-catalyzed Oxidation Of Hydrosilanesmentioning
confidence: 99%
“…Mechanism study based on spectroscopic techniques and the reaction kinetics shows that cationic tricarbonyl Mn(I) is the active species in the catalytic cycle (Scheme 5). [21] …”
Section: Transition‐metal‐catalyzed Hydroxylation Of Hydrosilanesmentioning
confidence: 99%